LEADERSHIP IN TOURISM AGENCY IN SELANGOR - Nur Hayatun Syamila, Mohd Nizam (Universiti Malaysia Sarawak (UNIMAS), 2021)
This paper is focus to explore the leadership among the employees at the private tourism agency in Selangor which is Al-Balad. This paper used qualitative approach in exploring and dig more about leadership in tourism agency in Selangor. The population used was three employees which were two females and one male. There were three main points or aspects identified in the research which are the importance of leadership towards work performance from the perspective of employees, the challenges of the current leadership in the tourism agency and the strategies to overcome the challenges. It was found that leadership is really important in the tourism agency and characters of a leader also play an important role especially in influencing their subordinates in performing their tasks. Hence, this research also found that the characters of a leader can influence how their subordinates response toward the challenges happened in the tourism agency. On the other hand, the research also contributes to the P-B Theory, employee, HR practitioner and to the tourism agency itself.